Fear arousal message in smoking cessation program among cardiovascular disease patients - Nurumal, Mohd. Said; Azmi, Junainah; Nik Mohamed, Mohamad Haniki; Ab Rahman, Norny Syafinaz; Firdaus, Mohd Khairul Zul Hasymi; Che Hasan, Muhammad Kamil; Jamaludin, Thandar Soe Sumaiyah (2020)
This video development is a part of the intellectual property (IP) required to be produced under the allocation of RIGS 15-087-0087 grant. The requirement for the development of this video is based on fear arousal message in smoking cessation program among cardiovascular disease patients. It is hoped that this new smoking cessation program will be a great benefit for future tobacco control program in our country. In addition, this new intervention can be integrated into the government policy and nursing practice to improve the cessation outcome especially for cardiac smokers in Malaysia.